Avaliação da estabilidade genética da uva cultivar itália (Vitis Vinifera L.) - Strioto, Danuza Kelly (2014)
The genus Vitis L. is not only highly diverse but is also distributed in many temperate and subtropical regions. The cultivar Italia (Vitis vinifera L.) by cross-breeding between Bicane and Moscatel de Hamburgo. Although grapes of the cultivar Italia are vegetally propagated, somatic mutations are rather frequent, with great genetic variability. Current research evaluated the genetic stability of the cultivar Italia by analyzing two different classes of DNA sequences, namely, the microsatellites or simple repeated sequences (SSR), and the regions between the simple repeated sequences (ISSR) of samples collected in three plantations in the municipality of Marialva and one in Sarandi PR Brazil. The first sequences were evaluated by using 13 pairs of primers. Loci studied registered 27 alleles (2.08 alleles/locus) and evidence of a reduced number of alleles. Polymorphism of the samples under analysis with SSR was 61.54%. Genetic diversity parameters indicated an increase of heterozygotes in the samples of the four accesses the cultivar Italia (negative rates of FIS were reported for 8 out of the 13 loci analyzed), with mean rate of FIS as -0.3404. Since FST rate was 0.0688, a moderate differentiation between accesses was indicated. Genetic similarity rates varied between 0.8516 (between accesses2 and 4) and 0.9884 (between accesses 1 and 3). The analysis of SSR sequences discriminated samples of the cultivar Italia and established the genetic stability of the samples of this cultivar. Fourteen primers were used for the study of ISSR sequences which amplified 135 DNA segments. The polymorphism for this marker was 80%. In spite of this high polymorphism, relationships of similarity and Nei genetic distance between the four accesses indicate low differentiation, with similarity rates ranging between 0.9503 (between accesses 1 and 4) and 0.9801 (between accesses 2 and 3). Genetic similarity rates calculated by the coefficient of Jaccard for 57 samples of the cultivar Italia ranged between 0.8358 and 1.0000. A Bayesian analysis performed for the two markers showed that the 57 plants of the 4 accesses were organized into 3 allele differential groups. Results show that the cultivar Italia has maintained itself genetically stable, provided by the number of alleles in 2006 (2.12 alleles) and in 2012 (2.08 alleles). With our results we cansee that the marker SSR allowed to discriminate the four accesses the cultivar Italy, contrary to the evidence that microsatellite markers are not suitable to discriminate genetically very similar samples, and that despite the high polymorphism present in ISSR sequences, this marker pointed to a low discrimination for plants of the four accesses collected